Factors associated with half- and full-marathon race-related injuries: A 3-year review - Mohseni, M. M.; Filmalter, S. E.; Taylor, W. C.; Vadeboncoeur, T. F.; Thomas, C. S. (Clinical Journal of Sport Medicine, 2021)
Objective: To better evaluate the relationships between training, demographics, and injury, this study sought to define race-related injury risk factors for half- and full-marathon runners.